Cho `P=(x^2 +x)/(x^2 -2x+1):((x+1)/x +1/(x-1)+(2-x^2)/(x^2-x))` Rút gọn `P`

Cho `P=(x^2 +x)/(x^2 -2x+1):((x+1)/x +1/(x-1)+(2-x^2)/(x^2-x))`
Rút gọn `P`

2 bình luận về “Cho `P=(x^2 +x)/(x^2 -2x+1):((x+1)/x +1/(x-1)+(2-x^2)/(x^2-x))` Rút gọn `P`”

  1. P=(x^2+x)/(x^2-2x+1):((x+1)/x+1/(x-1)+(2-x^2)/(x^2-x))(ĐK:x\ne0; x\ne1)
    P=(x.(x+1))/((x-1)^2):[(x+1)/x+1/(x-1)+(2-x^2)/(x.(x-1))]
    P=(x.(x+1))/((x-1)^2):((x+1).(x-1)+x+2-x^2)/(x.(x-1))
    P=(x.(x+1))/((x-1)^2):(x^2-1+x+2-x^2)/(x.(x-1))
    P=(x.(x+1))/((x-1)^2):(x+1)/(x.(x-1))
    P=(x.(x+1))/((x-1)^2).(x.(x-1))/(x+1)
    P=(x^2)/(x-1)
     

    Trả lời

Viết một bình luận

Câu hỏi mới